Life after COVID-19 : the other side of crisis - Parker, Martin (Bristol : Bristol University Press, 2020)
What might the world look like in the aftermath of COVID-19? Almost every aspect of society will change after the pandemic, but if we learn lessons then life can be better. Featuring expert authors from across academia and civil society, this book offers ideas that might put us on alternative paths for positive social change. A rapid intervention into current commentary and debate, Life After COVID-19 looks at a wide range of topical issues including the state, co-operation, work, money, travel and care. It invites us to see the pandemic as a dress rehearsal for the larger problem of climate change, and it provides an opportunity to think about what we can improve and how rapidly we can make changes.
Title from publisher's bibliographic system (viewed on 19 Mar 2021).
Keywords: COVID-19 (Disease) -- Social aspects; COVID-19 (Disease) -- Economic aspects